The United States of America: A Cornerstone of the World Gem Diamond Industry In the 20th Century - Levinson, A.; Cook, F. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary Throughout the 20th century, the United States has been the primary consumer of gem-quality diamonds. From the early 1900s to 1975, it consumed at least 50% of the world's diamond supply by both weight and value; from the late 1970s to 1999, its proportion of world consumption varied from about 40-67% by weight and about 28-48% by retail jewellery value, Japan is the only other country to qualify as a major consumer of gem diamonds in the 20th century and this has occurred only since 1972. As we enter the 21st century, gem diamond consumption continues its historic pattern of extreme reliance on the buying habits of orienation, i.e., the United States,